Hydrophobicity of Residue 128 of the Stress-Inducible Sigma Factor RpoS Is Critical for Its Activity - Iwase, Tadayuki; Matsuo, Takashi; Nishioka, Saiko; Tajima, Akiko; Mizunoe, Yoshimitsu (Frontiers in Microbiology, 2017)
RpoS is a key stress-inducible sigma factor that regulates stress resistance genes in Escherichia coli, such as the katE gene encoding catalase HPII and the glg genes encoding glycogen synthesis proteins. Monitoring RpoS activity can provide information on the stress sensitivity of E. coli isolates in clinical settings because the RpoS in these isolates is often mutated. In the present study, we found a novel, missense point mutation at RpoS residue 128 in a clinical Shiga toxin-producing E. coli (STEC) isolate. This mutation caused RpoS dysfunction and increased stress sensitivity. A mutant rpoS was cloned from a clinical STEC that is vulnerable to cold temperature and oxidative stresses. Mutant RpoS protein expression was detected in the clinical isolate, and this RpoS was non-functional according to HPII activity and glycogen levels, which are positively regulated by RpoS and thus are used as indicators for RpoS function. A reporter assay with β-galactosidase indicated that the dysfunction occurred at the transcriptional level of genes regulated by RpoS. Furthermore, substitution analysis indicated that the hydrophobicity of the amino acid at residue 128 was critical for RpoS activity; the simulation analysis indicated that the amino acids of RNA polymerase (RNAP) that interact with RpoS residue 128 are hydrophobic, suggesting that this hydrophobic interaction is critical for RpoS activity. In addition, substitution of Ile128 to Pro128 abolished RpoS activity, possibly as a result of disruption of the secondsary structure around residue 128, indicating that the structure is also a crucial factor for RpoS activity. These results indicate that only one point mutation at a hydrophobic residue of the complex formed during transcription leads to a critical change in RpoS regulation. Moreover, we found that Ile128 is widely conserved among various bacteria: several bacterial strains have Met128 or Leu128, which are hydrophobic residues, and these strains had similar or higher RpoS activity than that observed with Ile128 in this study. These data indicate that the hydrophobicity of the amino acid at residue 128 is critical for RpoS activity and is consequently important for bacterial survival. Taken together, these findings may contribute to a deeper understanding of protein functional mechanisms and bacterial stress responses.